CHALLENGES AND STRATEGIES IN E-GOVERNMENT IMPLEMENTATION IN A REMOTE REGION IN SUMENEP - Faris Anggara; Ika Devy Pramudiana; Eny Haryati; Sapto Pramono (Journal of Governance and Public Administration, 2025)
This study aims to analyze the challenges and strategies in implementing e-government in remote areas of Sumenep Regency. The approach used is qualitative with a case study design, which allows for an in-depth understanding of the obstacles and efforts that can be made in implementing digital government services. Data were collected through interviews with key stakeholders, direct observation of e-government infrastructure and utilization, and documentation studies. Data analysis was carried out using thematic analysis methods, including data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of e-government in Sumenep faces various challenges, such as limited information and communication technology (ICT) infrastructure, low digital literacy of the community, the digital divide between urban and rural areas, limited government human resource (HR) competency, and limited budget. In addition, resistance to change, lack of supporting local policies, and data security issues are also major obstacles. To overcome these obstacles, a comprehensive strategy is needed, such as improving ICT infrastructure through collaboration with the private sector, digital literacy programs for the community, strengthening government HR capacity, optimizing budget allocation, and cultural and social approaches to increase public acceptance of e-government. Continuous evaluation and monitoring are also needed to ensure the effectiveness of implementation. With the right strategy, e-government in Sumenep has the potential to improve the quality of public services and encourage a more inclusive and sustainable digital transformation. Keywords: E-Government, Ict Infrastructure, Digital Literacy, Digital Divide